Moderation of Nationalism on the Influence of Tax Payment Procedure Perspectives and Tax Law Compliance Perspective Towards Commitment to Becoming a Tax Compliant Accountant - Sihar Tambun; Indri Agustian Saputri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to prove the moderation of the attitude of nationalism on the effect of the tax payment procedure perspective and the tax law compliance perspective on the commitment to become a tax-abiding accountant. The sample used was 105 accounting students from various universities in Indonesia. The analytical method used is structural equation modeling using the help of Smart PLS software, both to test the direct effect and the effect of moderation. The results of the study prove that the attitude of nationalism has a significant effect on commitment to being a tax-abiding accountant. While the perspective of tax payment procedures has no significant effect on the commitment to become a tax-abiding accountant and the perspective of tax law compliance has a significant effect on the commitment to become a tax-abiding accountant.